Anode materials and lithium-ion batteries

By distributing silicon-based active materials in a carbon matrix with controlled aggregates and applying a coating, the volume expansion issue in silicon-based negative electrodes is mitigated, enhancing cycle stability and performance.

JP2025501831AActive Publication Date: 2025-01-24BTR NEW MATERIAL GRP CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024505629
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-14
Filing Date
2023-08-29
Publication Date
2025-01-24
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The challenge of silicon-based negative electrode materials in lithium-ion batteries is their significant volume expansion during the cycle process, leading to material pulverization and rapid cycle attenuation, which affects the battery's performance and stability.

Method used

The solution involves distributing active materials, such as silicon-based particles, within a carbon matrix with controlled ratios of primary particles, agglomerates, and aggregates, and applying a coating layer to suppress volume expansion and improve cycle stability.

Benefits of technology

This approach enhances the dispersion of active materials, improves carrier transport, and reduces volume expansion, resulting in improved cycle stability and rate performance of the negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501831000001_ABST
    Figure 2025501831000001_ABST
Patent Text Reader

Abstract

The present application provides a negative electrode material and a lithium ion battery. [Solution] The negative electrode material includes a composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles and / or agglomerates and aggregates, and a ratio of the aggregates to the total number of the primary particles, the agglomerates and the aggregates is 30% or less. The negative electrode material and lithium ion battery provided by the present application can reduce the volume expansion of the negative electrode material and improve the rate performance and cycle stability of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority from a Chinese patent application filed with the China Patent Office on December 14, 2022, bearing application number 2022116116483 and entitled "Negative Electrode Material and Lithium Ion Battery", the entire contents of which are incorporated herein by reference. This application relates to the technical field of anode materials, and in particular to anode materials and lithium ion batteries. [Background technology]

[0002] Electrified new energy vehicles are the future development direction of the automobile market, and their core components are lithium-ion batteries. With the development of the market, the demand for high capacity density batteries is increasing, and the adoption of new high specific volume positive and negative electrode materials is one of the important ways to increase the energy density of batteries.

[0003] More and more new materials such as metals, oxides, and metal alloys are being applied as active materials to anode materials to explore various ways to increase the energy density of batteries. Take silicon-based anode materials as an example. Silicon-based anode materials are one of the above active materials, and are generally considered to be the next generation of anode materials. They have ultra-high theoretical capacity (4200mAh / g) and low delithiation potential (<0.5V). Moreover, the voltage platform of silicon is slightly higher than that of graphite, and lithium surface deposition during charging is less likely to occur, and they are preferred due to their excellent safety. However, silicon anode materials have a rapid volume expansion effect during the cycle process, which leads to material pulverization and crushing, and the cycle decay of the battery is fast. At present, there are multiple solutions to this problem, including structural design for silicon, adopting technical means such as nanoization and porosity, and improving it through methods such as composite coating. However, designing various new silicon-carbon composite structures is one of the main directions of current improvement.

[0004] Therefore, suppressing the volume expansion of the negative electrode material and improving the cycle stability are urgent issues to be solved.

Summary of the Invention

Problems to be Solved by the Invention

[0005] This application provides a negative electrode material capable of reducing the volume expansion of the negative electrode material and improving the rate performance and cycle stability of the negative electrode material, and a lithium-ion battery.

Means for Solving the Problems

[0006] In a first aspect, this application provides a negative electrode material, the negative electrode material includes a composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles and / or agglomerates and aggregates, and the proportion of the aggregates in the total number of the primary particles, the agglomerates and the aggregates is 30% or less.

[0007] In some embodiments, the active material includes at least one of Li, Na, K, Sn, Ge, Si, SiOx (0 < x ≤ 2), Fe, Mg, Ti, Zn, Al, P, Cu, and silicon alloys.

[0008] In some embodiments, the active material includes a silicon-based active material, and the silicon-based active material includes at least one of crystalline silicon, amorphous silicon, and silicon alloys.

[0009] In some embodiments, the agglomerate is composed of a plurality of primary particles connected by a first connection method, and the first connection method includes at least one of corner-to-corner connection and side-to-corner connection.

[0010] In some embodiments, the proportion of the total number of the agglomerates and the primary particles in the total number of the primary particles, the agglomerates and the aggregates is 70% or more.

[0011] In some embodiments, the aggregate comprises a plurality of primary particles linked by a second linkage scheme, the second linkage scheme comprising at least one of edge-to-edge links and embedded links.

[0012] In some embodiments, the negative electrode material further comprises a coating layer present on at least a portion of the composite.

[0013] In some embodiments, the coating layer comprises at least one of a carbon layer, a graphene layer, a silicon nitride layer, a titanium nitride layer, and a silicon carbide layer.

[0014] In some embodiments, the coating layer has a thickness of 5 nm to 500 nm.

[0015] In some embodiments, the primary particles have a median diameter of 1 nm to 500 nm.

[0016] In some embodiments, the negative electrode material has a median diameter of 0.5 μm to 30 μm.

[0017] In some embodiments, the negative electrode material has a specific surface area of ​​10 m 2 / g or less.

[0018] In some embodiments, the negative electrode material has a porosity of 10% or less.

[0019] In some embodiments, the negative electrode material has a sphericity of 0.7 to 1.0.

[0020] In a second aspect, the present application provides a lithium-ion battery comprising the negative electrode material according to the first aspect. Effect of the Invention

[0021] The technical solution of the present application has at least the following beneficial effects: The negative electrode material provided by the present application has an active material dispersed in a carbon matrix, and the active material is bonded to the carbon matrix to achieve a uniform distribution in the carbon matrix. The active material includes primary particles and / or agglomerates and aggregates. The ratio of the number of aggregates present in the carbon matrix is ​​controlled to 30% or less, thereby effectively reducing the number of aggregated primary particles and improving the dispersion degree of the primary particles, thereby solving the problem of insufficient carrier transport between the aggregated primary particles, suppressing the volume expansion of the active material, and improving the cycle stability of the negative electrode material. [Brief description of the drawings]

[0022] The present application will now be further described with reference to the figures and examples. [Figure 1] FIG. 2 is a schematic diagram of primary particles, agglomerates, aggregates, a first connection mode, and a second connection mode in the negative electrode material provided by the present application. [Diagram 2] 1 is a scanning electron microscope (SEM) chart of the negative electrode material produced in Example 1 of the present application. [Diagram 3] 1 is an XRD chart of the negative electrode material prepared in Example 1 of the present application. [Figure 4] FIG. 2 is an initial charge / discharge curve diagram of a battery made of the negative electrode material prepared in Example 1 of the present application. [Diagram 5] FIG. 2 is a cycle characteristic curve diagram of a battery made of the negative electrode material produced in Example 1 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] It should be noted that the following are preferred embodiments of the embodiments of the present application, and those skilled in the art may make some modifications and improvements without departing from the principles of the embodiments of the present application, all of which fall within the scope of protection of the embodiments of the present application.

[0024] Specifically, the present application provides a negative electrode material, which includes a composite. The composite includes a carbon matrix and an active material present in the carbon matrix. The active material includes primary particles and / or agglomerates and aggregates. The proportion of aggregates in the total number of the above primary particles, the above agglomerates and the above aggregates is 30% or less.

[0025] The negative electrode material provided by the present application is such that the active material in the negative electrode material is dispersed in the carbon matrix, the active material is combined with the carbon matrix, a uniform distribution in the carbon matrix can be realized, and the active material includes primary particles and / or agglomerates and aggregates. By controlling the ratio of the number of aggregates present in the carbon matrix to 30% or less, the number of aggregated primary particles can be effectively reduced, the dispersity of the primary particles can be improved, thereby solving the problem that the carrier transport between the aggregated primary particles is not smooth, suppressing the volume expansion of the active material, and improving the cycle stability of the negative electrode material.

[0026] In some embodiments, the active material is a substance that can react with lithium and release / absorb lithium.

[0027] The active material includes at least one of a simple metal, a simple non-metal, a metal oxide, and a metal alloy. In some embodiments, the active material includes at least one of Li, Na, K, Sn, Ge, Si, SiOx (0 < x ≤ 2), Fe, Mg, Ti, Zn, Al, P, and Cu.

[0028] In some other embodiments, the active material may be a silicon alloy, such as a silicon-lithium alloy, a silicon-magnesium alloy, etc.

[0029] In some other examples, the active material may be an oxide, such as silicon monoxide. It should be noted that the active material may include at least two of a simple metal, a simple non-metal, a metal alloy, and a metal oxide.

[0030] In some embodiments, the active material comprises a silicon-based active material, the silicon-based active material comprising at least one of crystalline silicon, amorphous silicon, and a silicon alloy.

[0031] In some embodiments, the active material is granular, the active material comprising primary particles, agglomerates and aggregates, the mass percentage of the aggregates in the active material being 30% or less.

[0032] In some embodiments, primary particles refer to particles that are monodisperse under an electron microscope.

[0033] In some embodiments, the primary particles have a median diameter of 1 nm to 500 nm. Specifically, the median diameter may be 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, or 500 nm, and may of course be other values ​​within the above range, but is not limited thereto. Nano-order primary particles have high surface energy, tend to aggregate during charging and discharging, and have high granular structure, which can suppress the volume expansion of active particles. However, since nano-order active particles have large surface energy and tend to aggregate to form agglomerates or aggregates during charging and discharging, the primary particles are dispersed in the carbon matrix, which can reduce the aggregation effect. The active material has a too small particle diameter, and the manufacturing cost is high. The median diameter of the primary particles is preferably 1 nm to 200 nm, more preferably 1 nm to 100 nm.

[0034] In some embodiments, the agglomerates are comprised of a plurality of primary particles connected by a first connection manner, the first connection manner including at least one of corner-to-corner and side-to-corner connections, as shown in Figure 1. As will be appreciated, in an agglomerate, the primary particles are agglomerates of particles connected by a relatively loose connection manner.

[0035] In some embodiments, the ratio of the total number of agglomerates and primary particles to the total number of primary particles, agglomerates and aggregates is 70% or more. The agglomerates and aggregates are relatively dispersed, which is advantageous for mitigating volume expansion.

[0036] In some embodiments, the agglomerate includes a plurality of primary particles connected by a second connection manner, the second connection manner including at least one of edge-to-edge connections and embedded connections, as shown in Figure 1. In the agglomerate, the active material granules are connected relatively intimately to each other.

[0037] In addition, the primary particles in the agglomerates are all connected to each other by the first connection method, and the primary particles in the aggregates are connected to each other by at least two primary particles by the second connection method, that is, when the primary particles have both the first connection method and the second connection method, they are counted as aggregates. The contents of the primary particles, agglomerates, and aggregates in the negative electrode material are those observed from the cut surface by SEM.

[0038] In some embodiments, the primary particles, the agglomerates, and the aggregates are all embedded within a carbon matrix, and under the covering and blocking action of the carbon matrix, it is possible to prevent active materials of different shapes from generating an aggregation effect during charging and discharging, and to effectively utilize the buffering action of the carbon matrix to suppress the volume expansion of the active materials.

[0039] In some embodiments, the negative electrode material has a specific surface area of ​​10 m 2 / g or less, and the specific surface area of ​​the negative electrode material is specifically 10 2 / g, 9m 2 / g, 8m 2 / g, 7m 2 / g, 6m 2 / g, 5m 2 / g and 3m 2 / g, and of course, may be other values ​​within the above range, but is not limited thereto.

[0040] In some embodiments, the negative electrode material has a porosity of 10% or less, specifically, but not limited to, 0.5%, 0.7%, 0.9%, 1.5%, 2.0%, 3.5%, 5.0%, 6.5%, 7.5%, 8.0% or 10%. Controlling the porosity of the negative electrode material within the above range indicates that the electrolyte is less likely to penetrate into the material, which contributes to improving the stability of the negative electrode material. The porosity of the negative electrode material is preferably 5% or less, and more preferably 2.5% or less.

[0041] In some embodiments, the median diameter of the negative electrode material is 0.5 μm to 30 μm, and preferably, the median diameter of the negative electrode material may be specifically, but is not limited to, 0.5 μm, 1 μm, 5 μm, 10 μm, 11 μm, 12 μm, 13 μm, 15 μm, 17 μm, 18 μm, 19 μm, 20 μm, 25 μm, or 30 μm. In this particle size range, it is advantageous to obtain a product with a small specific surface area and a high tap density, which can reduce the loss of lithium ions, reduce irreversible capacity loss during charging and discharging, and improve the electrochemical performance of the negative electrode material.

[0042] In some embodiments, the negative electrode material further comprises a coating layer present on at least a portion of the composite.

[0043] In some embodiments, the coating layer includes at least one of a carbon layer, a graphene layer, a silicon nitride layer, a titanium nitride layer, and a silicon carbide layer. Specifically, the coating layer may be a carbon layer.

[0044] In some embodiments, the coating layer has a thickness of 5 nm to 500 nm. Specifically, the coating layer may have a thickness of 5 nm, 10 nm, 30 nm, 50 nm, 80 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, etc., and of course, may have other values ​​within the above ranges, but is not limited thereto.

[0045] In some embodiments, the negative electrode material is spherical or nearly spherical. Due to the spherical granule morphology, the negative electrode material has better tap density, high isotropy, low specific surface area, and low surface defects, so that the negative electrode material has higher press density, better charge and discharge performance, and the reversible capacity and initial efficiency of the negative electrode material are higher.

[0046] In some embodiments, the negative electrode material has a sphericity of 0.7 to 1.0, specifically, but not limited to, 0.7, 0.8, 0.85, 0.89, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, or 1.0, etc. In the present application, the sphericity refers to the ratio of the shortest diameter to the longest diameter of a granule.

[0047] The present application further provides a method for producing a negative electrode material, including the following steps S100 to S300. S100: mixing an oil solution containing active material primary particles with a second solution containing a carbon source precursor and a surfactant to obtain an emulsion, wherein the solvent in the second solution is incompatible with the oil solution; S200: drying and granulating the emulsion to obtain a precursor; S300: Mixing and coating the precursor with a second carbon source, and then carbonizing the mixture to obtain a negative electrode material.

[0048] The method for producing the negative electrode material provided in this application is as follows. The active material primary particles are first dispersed in an oil solution, and then the oil solution is mixed with a second solution containing a carbon source precursor and a surfactant to form an oil-in-water or oil-in-oil emulsion. The second solution contains a surfactant, so that the oil / solvent is incompatible, and the single small droplets are dispersed into smaller droplets, which can increase the dispersion degree of the active material primary particles. This can control the number of aggregates in the negative electrode material, effectively reduce the number of aggregated primary particles, solve the problem of the carrier transport between the aggregated primary particles being not smooth, and suppress the volume expansion of the active material, thereby improving the cycle stability of the negative electrode material.

[0049] This embodiment will be specifically described below. Before step S100, the method further includes: Preparing an oil solution containing primary particles of active material and a second solution containing a carbon source precursor and a surfactant.

[0050] As will be understood, the oil phase solvent is employed as the solvent in the oil solution, and the oil phase solvent and the solvent in the second solution are not compatible with each other.

[0051] In some embodiments, the oil phase solvent comprises at least one of an aromatic hydrocarbon-based compound, an aliphatic hydrocarbon-based compound, a halogenated hydrocarbon-based compound, an alcohol-based compound, an ether-based compound, an ester-based compound, a ketone-based compound, a glycol derivative-based compound, acetonitrile, pyridine, and phenol.

[0052] In some embodiments, the aromatic hydrocarbon compound comprises at least one of benzene, toluene, xylene, ethylbenzene, biphenyl, and styrene.

[0053] In some embodiments, the aliphatic hydrocarbon compound includes at least one of pentane, hexane, and octane.

[0054] The aliphatic hydrocarbon compound may be a straight-chain aliphatic hydrocarbon, a branched-chain aliphatic hydrocarbon, or an alicyclic hydrocarbon. Examples of the alicyclic hydrocarbon compound include cyclohexane, cyclopentane, cyclohexanone, toluene, and cyclohexanone.

[0055] In some embodiments, the halogenated hydrocarbon compound comprises at least one of chlorobenzene, dichlorobenzene, dichloromethane, and chloroform.

[0056] In some embodiments, the alcohol-based compound comprises at least one of n-butanol, n-pentanol.

[0057] In some embodiments, the ester compound includes at least one of methyl acetate, ethyl acetate, and propyl acetate.

[0058] In some embodiments, the ketone compound includes at least one of acetone, methyl butyl ketone, and methyl isobutyl ketone.

[0059] In some embodiments, the glycol derivative compound includes at least one of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether.

[0060] In some embodiments, the active material is a substance that reacts with lithium and can release and store lithium. The active material includes at least one of a simple metal, a simple nonmetal, a metal oxide, and a metal alloy.

[0061] In some embodiments, the active material includes at least one of Li, Na, K, Sn, Ge, Si, SiOx (0 < x ≤ 2), Fe, Mg, Ti, Zn, Al, P, and Cu.

[0062] In some other embodiments, the active material may be a silicon alloy, such as a silicon-lithium alloy, a silicon-magnesium alloy, etc. In some other examples, the active material may be an oxide, such as silicon monoxide. Note that the active material may include at least two of a simple metal, a metal alloy, and a metal oxide.

[0063] In some embodiments, the above active material includes a silicon-based active material, and the silicon-based active material includes at least one of crystalline silicon, amorphous silicon, and a silicon alloy.

[0064] In some embodiments, the active material primary particles have a median diameter of 1 nm to 500 nm, specifically, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, or 500 nm, etc., but of course, other values ​​within the above range may also be used, and are not limited thereto. The active material primary particles of nano-order have high surface energy, tend to aggregate during charging and discharging, and have high granular structure, which can suppress the volume expansion of the active material primary particles. However, the active material primary particles of nano-order have large surface energy, tend to aggregate during charging and discharging to form agglomerates or aggregates, so that the active material primary particles are dispersed in the carbon matrix, which can reduce the aggregation effect of the active material primary particles. The particle size of the active material primary particles is too small, which increases the cost of the production process. The active material primary particles have a median diameter of preferably 1 nm to 200 nm, more preferably 1 nm to 100 nm.

[0065] In some embodiments, the mass proportion of the active material primary particles in the oil solution is 8% to 38%, and specifically may be 8%, 10%, 12%, 15%, 18%, 20%, 25%, 30%, 35%, or 38%, etc., and of course may be other values ​​within the above range, but is not limited thereto.

[0066] In some embodiments, the carbon source precursor comprises at least one of sucrose, fructose, glucose, pitch, phenolic resins, polyimides, citric acid, polyvinyl alcohol, epoxy resins, polyurethanes, amino resins, polystyrene, polyimides, acrylic acid, polyacrylic acid, oxalic acid, citric acid, fatty acids, n-eicosanoic acid, polyethylene glycol, cyanoacrylates, acetylated hydroxypropyl cellulose, cellulose acetate butyrate, and the like.

[0067] In some embodiments, the surfactant comprises at least one of hexadecyltrimethylammonium bromide (abbreviated as CTAB), sodium linear alkylbenzene sulfonate (abbreviated as LAS), sodium fatty alcohol polyoxyethylene ether sulfate (abbreviated as AES), ammonium fatty alcohol polyoxyethylene ether sulfate (abbreviated as AES), sodium lauryl sulfate (abbreviated as SDS), lauroyl glutamic acid, polyoxyethylene nonylphenyl ether (abbreviated as TX-10), stearic acid monoglyceride, lignin sulfonate, heavy alkylbenzene sulfonate, alkyl sulfonate (petroleum sulfonate), sodium methylene dinaphthalene sulfonate (abbreviated as NNO), sodium methylene bis methyl naphthalene sulfonate (abbreviated as MF), alkyl polyether (PO-EO copolymer), and fatty alcohol polyoxyethylene ether (abbreviated as AEO-3).

[0068] In some embodiments, the solvent in the second solution comprises at least one of a polar aprotic organic phase, a polar protic organic phase, a non-polar organic phase, and water. In the above solvent, the polar aprotic organic phase, the polar protic organic phase, and the non-polar organic phase can form an oil-in-oil emulsion with the oil solution, and the water can form an oil-in-water emulsion with the oil solution, and in the mechanism of oil / solvent incompatibility, the single small droplets are dispersed smaller, and the dispersion degree of the active material primary particles can be improved, thereby controlling the number content of aggregates in the negative electrode material.

[0069] In some embodiments, the polar aprotic organic phase comprises N,N'-dimethylformamide (DMF), the polar protic organic phase comprises methanol, and the non-polar organic phase comprises at least one of octane, perfluorooctane, and perfluorohexane.

[0070] In some embodiments, the mass ratio of the oil solution to the second solution is (50-100):(40-70), and specifically, the mass ratio of the oil solution to the second solution may be, for example, 100:48, 70:40, 80:40, 50:70, or 50:50, and of course, may be other values ​​within the above range, but is not limited thereto.

[0071] In some embodiments, before the step of mixing the oil solution containing the active material primary particles with the second solution containing the carbon source precursor and the surfactant, the method further includes adding the active material primary particles to an oil phase solvent and dispersing the particles. By dispersing the particles, the active material primary particles in the oil solution can be dispersed, and aggregation of the active material primary particles can be reduced.

[0072] In some embodiments, before the step of mixing the oil solution containing the active material primary particles with the second solution containing the carbon source precursor and the surfactant, the method further includes dispersing the carbon source precursor and the surfactant in water, which can form a uniformly mixed solution.

[0073] In some embodiments, the dispersion process includes at least one of magnetic stirring, mechanical stirring, grinding dispersion, and ultrasonic dispersion. Preferably, grinding dispersion is adopted so that the active material primary particles can be dispersed, the active material primary particles can be reduced from agglomerating, and the active material can be dispersed into relatively small nanogranules. Preferably, by adopting a wet ball mill, the wet ball mill dispersion time can be controlled to 0.5h to 10h, specifically, it can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc., and of course, it can be other values ​​within the above range, but is not limited thereto. As can be understood, by grinding sufficiently, the fractions can be mixed more uniformly so that the particle size of the active material primary particles is 1nm to 500nm.

[0074] In step S100, an oil solution containing active material primary particles is mixed with a second solution containing a carbon source precursor and a surfactant to obtain an emulsion, wherein the solvent in the second solution is incompatible with the oil solution; In some embodiments, the mixing process of the oil solution and the second solution includes at least one of vacuum mixing and stirring mixing, which can make the dispersed active material primary particles adhere to the carbon source precursor and reduce the aggregation effect between the active material primary particles.

[0075] In some embodiments, the mixing process is performed in a homogenizer, and the mixing process time is 1 h to 10 h, specifically, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h, etc., or other values ​​within the above range, but is not limited thereto.

[0076] In step S200, the emulsion is dried and granulated to obtain a precursor.

[0077] In some embodiments, the drying temperature is 30°C to 400°C, specifically, 30°C, 40°C, 50°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 250°C, 280°C, 300°C, or 400°C, etc., the drying time is 1h to 15h, specifically, 1h, 3h, 5h, 7h, 9h, 10h, 12h, or 15h, etc., and the drying method may be, for example, oven drying, freeze drying, stirring evaporation to dryness, rotary evaporation to dryness, spray drying, etc., and in this embodiment, the solvent in the emulsion can be removed as much as possible by the drying treatment.

[0078] In step S300, the precursor is mixed with a second carbon source, coated, and then carbonized to obtain a negative electrode material.

[0079] In some embodiments, the second carbon source comprises at least one of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt.

[0080] In some embodiments, the mixing and coating apparatus includes at least one of a mechanical blender, a blender agitator, and a convection blender.

[0081] In some embodiments, the carbonization temperature is 600°C to 1200°C, and specifically may be 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc. Preferably, the carbonization temperature is 600°C to 1000°C.

[0082] In some embodiments, the time for the carbonization treatment is 1 h to 10 h, and specifically may be, but is not limited to, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h, etc.

[0083] In some embodiments, a protective gas is passed through during the carbonization process, and the protective gas includes at least one of nitrogen gas, helium gas, neon gas, argon gas, and krypton gas.

[0084] Furthermore, the method further includes sieving and demagnetizing the carbonized material to obtain a negative electrode material.

[0085] In some embodiments, the sieving method is any one of a fixed sieve, a drum screen, a resonating sieve, a roller sieve, a vibrating sieve, and a chain grizzly, and the mesh number of the sieving is 100 to 500 mesh. Specifically, the mesh number of the sieving may be 100 mesh, 200 mesh, 250 mesh, 325 mesh, 400 mesh, 500 mesh, etc., and preferably, the mesh number of the sieving is 250 mesh. Controlling the particle size of the negative electrode material within the above range is advantageous for improving the processing characteristics of the negative electrode material.

[0086] In some embodiments, the demagnetizing device is any one selected from a permanent magnet drum type magnetic separator, an electromagnetic separator, and a pulsating high gradient magnetic separator, and the demagnetizing is for ultimately controlling the magnetic material content of the negative electrode material so as to reduce the discharge effect of the magnetic material on the lithium ion battery and the impact on the safety of the battery during use.

[0087] The present application further provides a lithium ion battery using the negative electrode material according to the above embodiment of the present application or the negative electrode material manufactured by the manufacturing method of the negative electrode material according to the above embodiment of the present application. The lithium ion battery according to the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion.

[0088] The test method is as follows. 1) Method for measuring particle size of negative electrode material: Granule size test method refers to GB / T 19077-2016. It can be conveniently measured using a laser particle size analyzer, for example, Mastersizer 3000 type laser particle size analyzer from Malvern Ltd., UK. 2) Test method for specific surface area of ​​negative electrode material: After measuring the amount of gas adsorbed on a solid surface at different relative pressures at constant temperature and low temperature, the amount of sample monolayer adsorption is determined based on the Brunauer-Emmett-Teller adsorption isotherm theory and its equation (BET equation), and the specific surface area of ​​the material is calculated. 3) SEM measurements: Scanning electron microscopy characterization was carried out in a transmission electron microscope at an operating voltage of 200 kV to observe the structure of the anode material. 4) Coating thickness measurement method: The material is cross-sectioned by the FIB-SEM device and measured in the SEM to obtain the average thickness of the coating layer. 5) Method for determining the volume fraction of aggregates in material granules: Randomly select 20 pieces of the prepared negative electrode material for SEM cut surface, obtain the SEM cut surface of each negative electrode material granule, and count the number of primary particles in the cut surface, n A The number of agglomerates formed by a plurality of primary particles connected by the first connection method on the cut surface, n B The number of aggregates formed by a plurality of primary particles all connected in the second connection manner and connected in the first and second connection manners, n C Statistical analysis, P=n C / n A +n B +n C %, and the arithmetic mean value of the P values ​​of 20 negative electrode material granules is taken as the percentage of the number of aggregates. 6) Method for measuring the porosity of negative electrode material: The negative electrode material granules are measured using mercury intrusion porosimetry. 7) Method for measuring the mass content of amorphous carbon in negative electrode material: The mass content of amorphous carbon is determined by thermogravimetry. 8) Button battery testing The electrochemical cycle performance is measured by the following method. The prepared negative electrode material, conductive agent and adhesive are dissolved and mixed in water at a mass percentage of 94:1:5, the solid content is controlled to 50%, coated on a copper foil current collector, and vacuum dried to prepare a negative electrode sheet. Then, a ternary nickel cobalt manganese oxide lithium (NCM523) positive electrode sheet, 1mol / L LiPF6 / ethylene carbonate + dimethyl carbonate + methyl ethyl carbonate (v / v=1:1:1) electrolyte, Celgard2400 separator and housing are used to assemble to obtain a lithium ion battery. A micrometer is used to measure the initial thickness H0 of the electrode piece of the lithium ion battery, and the charge and discharge test of the lithium ion battery is performed at room temperature under a constant current of 0.2C in a LAND battery measurement system manufactured by Wuhan Jinnuo Electronics Co., Ltd., and the charge and discharge voltage is limited to 2.75 to 4.2V, and the initial reversible capacity, first cycle charge capacity and first cycle discharge capacity are obtained. First Coulombic Efficiency = First Cycle Discharge Capacity / First Cycle Charge Capacity.

[0089] After 50 cycles, the thickness of the pole piece of the lithium ion battery at this time was measured using a micrometer and designated as H1, and the expansion rate after 50 cycles was calculated as (H1-H0) / H0x100%.

[0090] After 100 cycles, the discharge capacity was recorded as the remaining capacity of the lithium-ion battery, and the capacity retention rate was calculated as remaining capacity / initial capacity×100%.

[0091] The present application will be further described below by dividing it into several examples. Note that the present application is not limited to the specific examples below. It can be modified as appropriate within the scope of the claims.

[0092] Example 1 The method for producing the negative electrode material includes the following steps (1) to (4). (1) Put nanosilicon into a ball mill, add n-butanol solvent, disperse in the ball mill for 5 hours, obtain an oil solution, the mass ratio of nanosilicon in the oil solution is 33%, the median diameter of nanosilicon is 103 nm, prepare an aqueous solution containing glucose and hexadecyltrimethylammonium bromide (CTAB), glucose:CTAB:water=44:2:100, obtain a second solution after stirring and dispersing. Then, put the oil solution and the second solution into a homogenizer in a mass ratio of 100:48 to perform homogenization, the homogenization time is 3 hours, and obtain a mixed emulsion; (2) The emulsion is stirred and dried, rotary evaporated to dryness at 200°C for 5 hours, and granulated to obtain the precursor. (3) Mix the precursor and phenolic resin in a mass ratio of 50:45, then put the mixed material into a high-temperature box furnace, introduce nitrogen gas, carbonize at 920°C, and keep the material warm for 4 hours. (4) Crushing, sieving and classifying the carbonization product to obtain the negative electrode material.

[0093] FIG. 2 is a scanning electron microscope (SEM) image of the negative electrode material prepared in Example 1, and FIG. 3 is an XRD image of the negative electrode material prepared in Example 1. As shown in FIGS. 2 and 3, the negative electrode material prepared in this example includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are silicon particles, the carbon layer has a thickness of 49 nm, and the quantity ratio of the aggregates in the active material is 20%.

[0094] Example 2 The method for producing the negative electrode material includes the following steps (1) to (4). (1) Put nanosilicon into a ball mill, add chloroform solvent, disperse in the ball mill for 3 hours, obtain an oil solution, the mass ratio of nanosilicon in the oil solution is 23%, the median diameter of nanosilicon is 82 nm, prepare an aqueous solution of sucrose and sodium alkylbenzene sulfonate, sucrose:sodium alkylbenzene sulfonate:water=54:1.2:100, obtain a second solution after stirring and dispersing, then put the oil solution and the second solution into a homogenizer in a mass ratio of 70:40 to perform homogenization, the homogenization time is 5 hours, and obtain a mixed emulsion; (2) The emulsion is stirred and dried, rotary evaporated to dryness at 400°C for 3 h, and granulated to obtain the precursor. (3) Mix the precursor and phenolic resin in a mass ratio of 56:45, then put the mixed material into a high-temperature box furnace, introduce nitrogen gas, carbonize at 820°C, and keep the material warm for 4 hours. (4) Crushing, sieving and classifying the carbonization product to obtain the negative electrode material.

[0095] The negative electrode material prepared in this example includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are silicon particles, the carbon layer has a thickness of 53 nm, and the quantity ratio of the aggregates in the active material is 14%.

[0096] Example 3 The method for producing the negative electrode material includes the following steps (1) to (4). (1) Put nanosilicon into a ball mill, add xylene solvent, disperse in the ball mill for 6 hours, obtain an oil solution, the mass ratio of nanosilicon in the oil solution is 13%, the median diameter of nanosilicon is 140 nm, prepare an aqueous solution of sucrose and sodium lauryl sulfate, sucrose:sodium lauryl sulfate:water=54:3.2:100, obtain a second solution after stirring and dispersing. Then, put the oil solution and the second solution into a homogenizer in a mass ratio of 80:40 to perform homogenization, the homogenization time is 5 hours, and obtain a mixed emulsion; (2) spray drying the emulsion and granulating it to obtain a precursor; (3) Mix the precursor and glucose in a mass ratio of 56:65, then put the mixed material into a high-temperature box furnace, introduce nitrogen gas, carbonize at 780°C, and keep warm for 4 hours; (4) Crushing, sieving and classifying the carbonization product to obtain the negative electrode material.

[0097] The negative electrode material prepared in this example includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are silicon particles, the carbon layer has a thickness of 58 nm, and the quantity ratio of the aggregates in the active material is 26%.

[0098] Example 4 The method for producing the negative electrode material includes the following steps (1) to (4). (1) Put nanosilicon into a ball mill, add n-hexane solvent, disperse in a ball mill for 12 hours, obtain an oil solution, the mass ratio of nanosilicon in the oil solution is 38%, the median diameter of nanosilicon is 55 nm, prepare an aqueous solution of polyvinyl alcohol and lauroyl glutamic acid, polyvinyl alcohol: lauroyl glutamic acid: water = 54: 2.9: 100, obtain a second solution after stirring and dispersing. Then, put the oil solution and the second solution into a homogenizer in a mass ratio of 50: 70 to perform homogenization, the homogenization time is 2 hours, and obtain a mixed emulsion; (2) spray drying the emulsion and granulating it to obtain a precursor; (3) Mix the precursor and asphalt in a mass ratio of 68:40, then put the mixed material into a high-temperature box furnace, introduce nitrogen gas, carbonize at 1020°C, and keep the material warm for 3 hours. (4) Crushing, sieving and classifying the carbonization product to obtain the negative electrode material.

[0099] The negative electrode material prepared in this example includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are silicon particles, the carbon layer has a thickness of 49 nm, and the quantity ratio of the aggregates in the active material is 18%.

[0100] Example 5 The method for producing the negative electrode material includes the following steps (1) to (4). (1) Put nanosilicon into a ball mill, add propylene oxide solvent, disperse in the ball mill for 6 hours, obtain an oil solution, the mass ratio of nanosilicon in the oil solution is 8%, the median diameter of nanosilicon is 38 nm, prepare an aqueous solution of citric acid and aliphatic alcohol polyoxyethylene ether, citric acid: aliphatic alcohol polyoxyethylene ether: water = 64: 2.5: 100, obtain a second solution after stirring and dispersing, then put the oil solution and the second solution into a homogenizer in a mass ratio of 50: 50 to perform homogenization, the homogenization time is 4 hours, and obtain a mixed emulsion; (2) spray drying the emulsion and granulating it to obtain a precursor; (3) Mix the precursor and sucrose in a mass ratio of 48:60, then put the mixed material into a high-temperature box furnace, introduce nitrogen gas, carbonize at 980°C, and keep the temperature for 3 hours. (4) Crushing, sieving and classifying the carbonization product to obtain the negative electrode material.

[0101] The negative electrode material prepared in this example includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are silicon particles, the carbon layer has a thickness of 52 nm, and the quantity ratio of the aggregates in the active material is 8%.

[0102] Example 6 The difference from Example 1 is that in step (1), the active materials added are nanosilicon and silicon-magnesium alloy.

[0103] The negative electrode material prepared in this embodiment includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are silicon particles and silicon magnesium alloy particles, the carbon layer has a thickness of 48 nm, and the quantity ratio of the aggregates in the active material is 18%.

[0104] Example 7 The difference from Example 1 is that the active material added in step (1) is nano-silicon monoxide.

[0105] The negative electrode material prepared in this example includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are SiO, the carbon layer has a thickness of 52 nm, and the quantity ratio of the aggregates in the active material is 22%.

[0106] Example 8 The difference from Example 1 is that the active material added in step (1) is Ge.

[0107] The negative electrode material prepared in this example includes a composite and a carbon layer present on the surface of the composite, the composite includes a carbon matrix and an active material present in the carbon matrix, the active material includes primary particles, agglomerates and aggregates, the primary particles are germanium particles, the carbon layer has a thickness of 48 nm, and the quantity ratio of the aggregates in the active material is 19.4%.

[0108] Example 9 The method for producing the negative electrode material includes the following steps (1) to (4). (1) Put nanosilicon into a ball mill, add n-butanol solvent, disperse in the ball mill for 5 hours, obtain an oil solution, the mass ratio of nanosilicon in the oil solution is 25%, the median diameter of nanosilicon is 98 nm, prepare an aqueous solution containing glucose and hexadecyltrimethylammonium bromide (CTAB), glucose:CTAB:water=44:2:100, obtain a second solution after stirring and dispersing. Then, put the oil solution and the second solution into a homogenizer in a mass ratio of 100:48 to perform homogenization, the homogenization time is 3 hours, and obtain a mixed emulsion; (2) The emulsion is stirred and dried, rotary evaporated to dryness at 200°C for 6 hours, and granulated to obtain the precursor. (3) The precursor is placed in a high-temperature box furnace, nitrogen gas is introduced, and the precursor is carbonized at 920°C. The precursor is then carbonized for 4 hours and kept at that temperature. (4) Crushing, sieving and classifying the carbonization product to obtain the negative electrode material.

[0109] The negative electrode material prepared in this example includes a composite, the composite including a carbon matrix and an active material present within the carbon matrix, the active material including primary particles, agglomerates and aggregates, the primary particles being silicon particles, the carbon layer having a thickness of 25 nm, and the quantity proportion of the aggregates in the active material being 24%.

[0110] Comparative Example 1 The difference from Example 1 is that in step (1), no surfactant was added to the second solution.

[0111] The negative electrode material prepared in this example includes a composite, the composite including a carbon matrix and an active material present within the carbon matrix, the active material including primary particles, agglomerates and aggregates, the primary particles being silicon particles, the carbon layer having a thickness of 44 nm, and the quantity ratio of the aggregates in the active material being 39%.

[0112] Comparative Example 2 The difference from Example 1 is that no dispersion process was carried out in step (1).

[0113] The negative electrode material prepared in this example includes a composite, the composite including a carbon matrix and an active material present within the carbon matrix, the active material including primary particles, agglomerates and aggregates, the primary particles being silicon particles, the carbon layer having a thickness of 45 nm, and the quantity proportion of the aggregates in the active material being 43%.

[0114] Comparative Example 3 The differences from Example 1 are as follows: (1) Put nanosilicon into a ball mill, add water solvent, and disperse in the ball mill for 5 hours to obtain a first solution, the mass ratio of nanosilicon in the first solution is 39%, the median diameter of nanosilicon is 107 nm, prepare an aqueous solution containing glucose and hexadecyltrimethylammonium bromide (CTAB), glucose:CTAB:water=44:2:100, and obtain a second solution after stirring and dispersing. Then, put the first solution and the second solution into a homogenizer in a mass ratio of 100:48 to perform homogenization, the homogenization time is 3 hours, and obtain a mixed solution.

[0115] The negative electrode material prepared in this example includes a composite, the composite including a carbon matrix and an active material present within the carbon matrix, the active material including primary particles, agglomerates and aggregates, the primary particles being silicon particles, the carbon layer having a thickness of 45 nm, and the quantity proportion of the aggregates in the active material being 34%.

[0116] The negative electrode materials produced in the examples and comparative examples were subjected to performance tests, and the results of the performance tests are shown in Table 1.

[0117] [Table 1]

[0118] FIG. 4 is a first charge / discharge curve of the negative electrode material prepared in Example 1 of the present application. As shown in FIG. 4, the negative electrode material prepared in Example 1 has a high first charge / discharge capacity and a high first efficiency. This is because the aggregated primary particles affect the carrier transport between the primary particles. In the present application, the ratio of the number of aggregates in the negative electrode material is controlled within a preset range, which can effectively improve the carrier transport inside the granules of the composite, and the negative electrode material has excellent electrochemical performance.

[0119] 5 is a cycle performance curve of the negative electrode material prepared in Example 1 of the present application, as shown in Fig. 5, the negative electrode material has excellent cycle performance, and the capacity retention rate after 100 cycles is 93.5%. This is because the active material is present in the carbon matrix, which can effectively buffer the volume expansion of the active material dispersed in the carbon matrix, reduce the stress change caused by the expansion of the active material, improve the cycle stability of the material, and reduce the expansion rate.

[0120] As shown in Table 1, the negative electrode materials prepared in Examples 1 to 9 include a composite, the composite includes a carbon matrix and an active material present in the carbon matrix, and the active material includes primary particles, agglomerates, and aggregates. The ratio of the number of aggregates in the active material is 30% or less, which can effectively improve the transport of carriers inside the granules of the composite, effectively improve the structural stability of the material, and reduce the stress change caused by the expansion of the active material, thereby improving the cycle stability performance of the material and reducing the expansion rate.

[0121] In the manufacturing process of the negative electrode material of Comparative Example 1, no surfactant is added to the second solution, which results in uneven dispersion of nanosilicon and easy formation of agglomerates, resulting in a high proportion of agglomerates in the final product, poor electrochemical performance, and a significant increase in the battery expansion rate.

[0122] In the manufacturing process of the negative electrode material of Comparative Example 2, no dispersion treatment was performed, and the nanosilicon particles naturally aggregated. This resulted in a high proportion of aggregates in the final product, which in turn deteriorated the electrochemical performance and significantly increased the battery expansion rate.

[0123] In the manufacturing process of the negative electrode material of Comparative Example 3, in step (1), the active material is dispersed in an aqueous solution, and the aqueous solution and the second solution are homogenized to obtain a mixed solution. When dispersion is performed in an aqueous phase system, the nanosilicon is easily oxidized and the initial efficiency decreases, while the dispersion effect of the aqueous solution is not as good as that of an oil-water system, the proportion of aggregates in the final product is high, and the electrochemical performance is not as good as that of an oil-water system.

[0124] Although the present application has been disclosed by the above preferred embodiments, it does not limit the scope of the claims, and any person skilled in the art may make some possible changes or modifications without departing from the technical idea of ​​the present application, so the scope of protection of the present application should conform to the scope defined in the appended claims.

Claims

1. A negative electrode material comprising a composite, The composite includes a carbon matrix and an active material present within the carbon matrix; The active material comprises primary particles and / or agglomerates and aggregates, a ratio of said aggregates to a total number of said primary particles, said agglomerates and said aggregates is 30% or less.

2. The active material is Li, Na, K, Sn, Ge, Si, SiO x 2. The negative electrode material of claim 1, comprising at least one of: (0<x≦2), Fe, Mg, Ti, Zn, Al, P, Cu, and a silicon alloy.

3. 2. The negative electrode material of claim 1, wherein the active material comprises a silicon-based active material, the silicon-based active material comprising at least one of crystalline silicon, amorphous silicon, and a silicon alloy.

4. The negative electrode material according to claim 1, characterized in that it has at least one of the following characteristics (1) to (2). (1) the agglomerates are comprised of a plurality of primary particles connected in a first connection manner, the first connection manner including at least one of corner-to-corner and side-to-corner connections; (2) The ratio of the total number of the agglomerates and the primary particles to the total number of the primary particles, the agglomerates, and the aggregates is 70% or more.

5. 2. The anode material of claim 1, wherein the aggregate comprises a plurality of primary particles connected by a second connectivity manner, the second connectivity manner comprising at least one of edge-to-edge connectivity and embedded-type connectivity.

6. 10. The negative electrode material of claim 1, further comprising a coating layer present on at least a portion of the composite.

7. The negative electrode material according to claim 6, wherein the coating layer has at least one of the following characteristics (1) to (2): (1) the coating layer includes at least one of a carbon layer, a graphene layer, a silicon nitride layer, a titanium nitride layer, and a silicon carbide layer; (2) The coating layer has a thickness of 5 nm to 500 nm.

8. 2. The negative electrode material according to claim 1, wherein the primary particles have a median diameter of 1 nm to 500 nm.

9. The negative electrode material according to any one of claims 1 to 8, characterized in that it has at least one of the following characteristics (1) to (4). (1) The negative electrode material has a median diameter of 0.5 μm to 30 μm; (2) The negative electrode material has a specific surface area of ​​10 m 2 / g or less; (3) The negative electrode material has a porosity of 10% or less; (4) The negative electrode material has a sphericity of 0.7 to 1.

0.

10. A lithium ion battery comprising the negative electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silicon-carbon anode material and preparation method thereof, anode and battery

    CN109449401A

  • Silicon nanocomposite nanofibers

    JP2015516516A

  • Si / G / C Composite for Lithium-Ion Batteries

    JP2017506413A

  • Powders, electrodes and batteries containing such powders

    JP2018501620A

  • Manufacturing method of Si / C composite particles

    JP2019511444A